The crystal structure and transformations of the omicron phase Ο in the Ti-Al-Nb system and on the ambiguity of its subvariants Ο1 and Ο2. (October 2022) - Xu, Shuai; Reid, Mark; Lin, Junpin; Liang, Yongfeng; Yang, Liang; Zhang, Jinhu; Liss, Klaus-Dieter
Abstract: Omicron, Ο-Ti2 NbAl alloys have been under continuous development for more than 40 years as potential materials for the gas turbine engine; however, the crystal structure and phase transformations are still unclear. In this work, we clarified the crystal structure, atom positions and phase transformations of the Ο phase by in-situ neutron diffraction and high-temperature X-ray diffraction methods. From room temperature to the vanishing temperature of the Ο phase, the latter exposes a C m c m structure, with Ti and Nb atoms tending to respectively occupy the 8g and 4c2 positions, but with a certain disorder, introducing an order parameter. The phase transformation sequences of Ti-24.8Al-24.3Nb alloy are Ο(975 °C) → βo + Ο(997.5 °C) → βo (1165.5 °C) → β. Moreover, we have proven that a distinction of the omicron subvariants Ο1 and Ο2 is crystallographic nonsense as Ο1 must equal to α2 of P 63 /m m c structure, and Ti2 NbAl is a prototype structure by itself. Graphical abstract: Image, graphical abstract